Linking Methane Emissions to Iron Dynamics in Bioturbated Rice Systems - Huangfu, Qianrui; Zhang, Sha; Chen, Zheng; Wang, Lu; Zhu, Dong (浪淘沙预印本平台, 2026)
Iron (Fe) redox cycling is intricately linked to methane (CH₄) emissions in global wetlands, yet its role under sustained bioturbation remains poorly quantified. We investigated how continuous loach (Misgurnus anguillicaudatus) activity influences CH₄ emissions and Fe dynamics in a ratoon rice system over 178 days. Methane and ecosystem CO₂ fluxes were measured continuously, while in situ microdialysis quantified dissolved Fe in surface and root-zone porewaters. The results showed that loach bioturbation increased cumulative CH₄ emissions by 31.9% (95% CI: [18.2%, 40.2%], p = 0.0033) and sustained elevated dissolved Fe concentrations near the soil–water interface (SWI), indicating intensified reducing conditions and a weakened SWI barrier for CH₄. A Fe-based process model alone explained >78% of CH₄ flux variability. A more integrated model further suggested that loach activity enhanced CH₄ emissions by increasing labile carbon supply, CH₄ production efficiency, and CH₄ transport. These findings position dissolved Fe as a practical proxy for CH₄ emissions, with implications on improving global CH₄ models.